Peran Selenium dan Vitamin E pada Ruminansia: ulasan singkat: The Role of Selenium and Vitamin E in Ruminants: A Brief Review - Yanuartono; Indarjulianto, Soedarmanto; Paryuni, Alsi Dara (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: Selenium (Se) is an element commonly found in nature. Selenium is found in the soil and is absorbed by plants at different levels depending on plant species, fertilizer use, and rainfall, while vitamin E is abundant in legume plants and fresh grass. Selenium and vitamin E are essential elements for ruminants and are needed for average growth and help prevent other health problems. The roles of these two elements are closely related because they can protect cells from the detrimental effects of oxidation, even though they have different mechanisms. Deficiency of one or both elements can cause white muscle disease, retained placenta, metritis, decreased immune function, and mastitis. However, research and field studies also show that Se and vitamin E can cause poisoning in ruminants. Reviews : This article will briefly review the impact of Se Vitamin E deficiency and toxicity on ruminants.